Compensation of subjects for participation in biomedical research in resource – limited settings: a discussion of practices in Malawi - Nyangulu, Wongani; Mungwira, Randy; Nampota, Nginanche; Nyirenda, Osward; Tsirizani, Lufina; Mwinjiwa, Edson; Divala, Titus (BMC medical ethics, 2019)
Compensating participants of biomedical research is a common practice. However, its proximity with ethical concerns of coercion, undue influence, and exploitation, demand that participant compensation be regulated. The objective of this paper is to discuss the current regulations for compensation of research participants in Malawi and how they can be improved in relation to ethical concerns of coercion, undue influence, and exploitation. In Malawi, national regulations recommend that research subjects be compensated with a stipend of US$10 per study visit. However, no guidance is provided on how this figure was determined and how it should be implemented. While necessary to prevent exploitation, the stipend may expose the very poor to undue influence. The stipend may also raise the cost of doing research disadvantaging local researchers and may have implications on studies where income stipend is the intervention under investigation. We recommend that development and implementation of guidelines of this importance involve interested parties such as the research community and patient groups. Compensating human research subjects is important but can also act as a barrier to voluntary participation and good research efforts. Deliberate measures need to be put in place to ensure fair compensation of research participants, avoid their exploitation and level the field for locally funded research.